2015
DOI: 10.15226/csroa.2015.00117
|View full text |Cite
|
Sign up to set email alerts
|

CA215, A New Pan Cancer Biomarker, and its Clinical Applications

Abstract: The antigen recognized by RP215, CA215, can be detected in the shed media from a number of cultured cancer cells [2,5]. Therefore, Matrix-Assisted Laser Desorption/Ionization TimeOf-Flight Mass Spectrometry (MALDI-TOF MS) analysis was performed to determine the molecular identity of affinityisolated CA215 from the shed media of OC-3-VGH ovarian and C-33A cervical cancer cell lines [2,5]. Following tryptic digestion of CA215, the peptide fragments were subjected to analysis by MALDI-TOF MS. It was observed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Liang et al have shown IgG to inhibit cell apoptosis and induce cell growth and multiplication in urothelial carcinoma . The serum levels of CA215, immunoglobulin secreted by cancer cells, is under clinical trials as diagnostic marker for detecting and observing the cancers of ovaries and cervix by RP215 monoclonal antibody that specifically associates with the variable region of CA215 . Many studies have established the phenomenon of Ig heavy chains (especially IgG class) expression by cancer cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Liang et al have shown IgG to inhibit cell apoptosis and induce cell growth and multiplication in urothelial carcinoma . The serum levels of CA215, immunoglobulin secreted by cancer cells, is under clinical trials as diagnostic marker for detecting and observing the cancers of ovaries and cervix by RP215 monoclonal antibody that specifically associates with the variable region of CA215 . Many studies have established the phenomenon of Ig heavy chains (especially IgG class) expression by cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…163 The serum levels of CA215, immunoglobulin secreted by cancer cells, is under clinical trials as diagnostic marker for detecting and observing the cancers of ovaries and cervix by RP215 monoclonal antibody that specifically associates with the variable region of CA215. [170][171][172][173] Many studies have established the phenomenon of Ig heavy chains (especially IgG class) expression by cancer cells. With few exceptions, Ig light chains are also expressed though at lower levels than the heavy chains.…”
Section: Figurementioning
confidence: 99%
“…CA215 (0.1Au/mL) a: the concentration in each bracket ( ) is the cut-off value for each respective cancer biomarker; b: n refers to the number of patient cases; c: I: CA215 only; d: II: other marker only; e: III: combined, modified taken from [19] with permission. Table 1: Comparative positive detection rates of various cancers by CA215-based and other cancer-associated antigen-based enzyme immunoassay kits [17,37].…”
Section: Immunodiagnostic Application Of Rp215 For Monitoring Serum Cmentioning
confidence: 99%
“…In view of the fact that CA215 contains multiple epitope recognized by RP215, this monoclonal antibody can serve simultaneously both for capturing and signal detection of CA215 in a sandwich enzyme immunoassay for the monitoring of serum CA215 levels among cancer patients [17,18].…”
Section: Immunodiagnostic Application Of Rp215 For Monitoring Serum Cmentioning
confidence: 99%
“…In addition, elevation of CA215 levels in human serum of cancer patients could be routinely monitored by RP215-based immunoassays [2]. Results indicate that CA215 can serve as a pan cancer marker similar to those used clinically, such as CA125, CA15-3 and CA199 [11,[16][17][18][19][20][21][22]. Therefore, in this short review, mechanisms of action studies of RP215 on cancer cells were summarized and reviewed for potential immunodiagnostic and immunotherapeutic applications.…”
Section: Introductionmentioning
confidence: 99%